Temporal trend of mortality from infectious respiratory diseases in childhood in Minas Gerais, Brazil, 2000-2020 - Davi Nilson Aguiar e Moura; Fillipe Reis Silva; David Morosini de Assumpção; Nícolas Emanuel Oliveira Reis; Isabela Fernandes Coelho Cunha; Amanda Priscila de Santana Cabral Silva; Waneska Alexandra Alves (Ministério da Saúde do Brasil, 2023)
ABSTRACT Objective: to analyze temporal trends in mortality due to infectious respiratory disease in children under 12 years old in Minas Gerais, Brazil, from 2000 to 2020. Methods: this was an ecological study using data on infectious respiratory disease in children under 12 years old registered on the Mortality Information System; the variables studied were etiological agent, anatomical site of infection and sex; trends were analyzed by joinpoint regression. Results: of the 4,688 registered deaths, the etiological agent of the disease was unspecified for 84.5% of them, and 88% were due to lower respiratory tract infections; there was a decreasing trend in deaths and in the proportion of deaths due to unspecified etiologic agents; in 2020, there was an increase in deaths with viral etiology and systemic involvement. Conclusion: in addition to the change in the etiologic profile, there was a reduction in mortality due to infectious respiratory diseases in children, even considering 2020, the year of the COVID-19 pandemic.